2020
DOI: 10.1115/1.4046420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lattice Setting Density on Fluid Flow and Convective Heat Transfer Characteristics of Bricks in Tunnel Kilns

Abstract: This paper reports the effect of setting density on flow uniformity, pressure drop, pumping power, and convective heat transfer coefficients (CHTCs). High-density setting (HDS) comprises 768 bricks, and low-density setting (LDS) contains 512 bricks are tested for different inlet air velocities using both local and average approaches. The investigation is carried out using a 3D-computational fluid dynamics (CFD) model with k–ω turbulence model. Both settings are validated against experimental data reported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The HDS was composed of 768 bricks, whereas the LDS contained 512 bricks, i.e., the HDS had 50% more bricks than the LDS. The authors [51] reported higher convective heat transfer coefficients and a lower pressure drop in the LDS than the HDS. Additionally, the LDS provided more consistent and more multifaceted convection heat transfer coefficients than the HDS.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…The HDS was composed of 768 bricks, whereas the LDS contained 512 bricks, i.e., the HDS had 50% more bricks than the LDS. The authors [51] reported higher convective heat transfer coefficients and a lower pressure drop in the LDS than the HDS. Additionally, the LDS provided more consistent and more multifaceted convection heat transfer coefficients than the HDS.…”
Section: Introductionmentioning
confidence: 90%
“…However, those papers did not explicitly investigate the effect of the setting density. A comprehensive project started in 2016 by the same research team as for this paper aimed to enhance the tunnel kiln performance by developing reliable design data for tunnel kilns [29,33,34,51,52]. Accurate three-dimensional CFD models were developed, using the k-ω turbulence model to study the different aspects of the tunnel kilns, including the flow uniformity [29], convection heat transfer [33,34], setting density [51], and surface roughness [52] of the bricks and kiln boundaries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bustos et al [99] carried out this type of simulation for the elaboration of charcoal in a brick kiln, and their results provide important information for the improvements in the kiln operation and allow establishment of consistent initial conditions of temperature and heat flux for kinetics models for charcoal cooling in kilns. Alrahmani et al [100] researched the effect of lattice setting density on fluid flow and convective heat transfer characteristics of bricks in Tunnel Kilns, using a 3D-computational fluid dynamics model with k-ω turbulence model. The computational simulations allowed that the authors report the effect of setting density on flow uniformity, pressure drop, pumping power and convective heat transfer coefficients.…”
Section: Future Trends About Phenomenological Studiesmentioning
confidence: 99%